Efeitos colaterais do ''fomento industrial'' : o exemplo do subsector português do volfrâmio até à década de 1950 - Nunes, João Paulo Avelãs (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this article, one intends to characterise and analyse the way in which, in Mainland Portugal, from the 1870s to the 1950s, and in the mining tungsten sub-sector, the relationship between industrial or artisanal activity and neighbouring rurality was structured, in aspects such as the working and living conditions, work accidents and illnesses, pollution and the type of integration into the global economy. More than judging or taking a stand on the object of study, one seeks to describe and explain, contextualising, the traits of “normality” and of “exceptionality”, the permanences and mutations detected.